Dietary habits and selected noncommunicable disease risk factors among middle-aged adults in rural Kerala - M., Balasankar J.; K., Hanudha N.; S., Neethu M.; Soman, Biju (International Journal Of Community Medicine And Public Health, 2023)
Background: Noncommunicable disease (NCD) risk factors are increasing in Kerala. The science of Ayurveda emphasizes lifestyle modification rather than treating the disease. We aim to explore the correlation between selected ayurvedic dietary risk factors with NCD risk factors like hypertension, diabetes, dyslipidemia and obesity. Methods: Using cluster sampling, a community-based cross-sectional study was conducted among 410 middle-aged adults in the rural Kollam district, Kerala. The participants underwent biochemical tests for fasting blood sugar (FBS) and serum cholesterol (S. Cholesterol). WHO STEPs questionnaire, food frequency questionnaire (FFQ), and a checklist to assess the usage of dietary risk factors proposed by Ayurveda for NCDs were used. All analyses were done using R software version 4.1.2. Results: The mean age of the participants was 46±5.4 years. The rates of regular intake of salty foods (ati-lavana) (77.1%), sour foods (ati-amla) (80.5%), heavy foods (guru-annapaana) (87.3%), oily foods (snigdha annapaana) (67.3%), frequency of food intake more than 4 times day (80%) were found to be high in population. On multivariate analysis, increased frequency of food intake was found to be associated with diabetes (AOR-1.9, CI: 1.2-3.2). Conclusions: Some of the risk factors that Ayurveda has been proposing are found to have an association with the NCD risk factors considered. Interventions to reduce the prevalence of selected NCD risk factors that incorporate the stipulations of alternative systems could have a significant public health impact.